2022
DOI: 10.3390/molecules27144644
|View full text |Cite
|
Sign up to set email alerts
|

Inosine in Neurodegenerative Diseases: From the Bench to the Bedside

Abstract: Neurodegenerative diseases, such as Alzheimer′s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and multiple sclerosis (MS), currently represent major unmet medical needs. Therefore, novel therapeutic strategies are needed in order to improve patients’ quality of life and prognosis. Since oxidative stress can be strongly involved in neurodegenerative diseases, the potential use of inosine, known for its antioxidant properties, in this context deserves particular attention. The prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Specially, Oxaloacetic acid can stimulate neurogenesis and activate brain mitochondrial biogenesis [74] . Inosine (Supplementary Figure 7C) was thought to be a potential strategy of neurodegenerative diseases treatment [75,76] . S-Adenosyl-Lhomocysteine(Supplementary Figure 7D) were significantly increased in ASD [77] and this metabolite can be quickly linked to the glutamic acid-homocysteine metabolic network in Figure 6a as L-homocysteine is the precursor of S-Adenosyl-Lhomocysteine.…”
Section: Rfw Enlightened Us More Insights Into Associations Between M...mentioning
confidence: 99%
“…Specially, Oxaloacetic acid can stimulate neurogenesis and activate brain mitochondrial biogenesis [74] . Inosine (Supplementary Figure 7C) was thought to be a potential strategy of neurodegenerative diseases treatment [75,76] . S-Adenosyl-Lhomocysteine(Supplementary Figure 7D) were significantly increased in ASD [77] and this metabolite can be quickly linked to the glutamic acid-homocysteine metabolic network in Figure 6a as L-homocysteine is the precursor of S-Adenosyl-Lhomocysteine.…”
Section: Rfw Enlightened Us More Insights Into Associations Between M...mentioning
confidence: 99%
“…However, they also suggested that phase III trials with a longer follow-up period, of more than 1 year, may be needed to evaluate the efficacy of inosine in preventing disease recurrence and progression ( 62 ). Given the results of preclinical and clinical studies of inosine use, the most important properties of inosine seem to be its antioxidant actions and its potential to increase energy resources by improving adenosine triphosphate availability ( 63 ). Table 5 summarized the evidence of investigating the relationship between multiple sclerosis and serum uric acid levels ( 40 42 , 51 , 52 , 56 ).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Urate, the metabolite of inosine, is an endogenous antioxidant and potential neuroprotectant. Its level is lower in patients with ALS, and a high urate level is associated with improved survival ( Basile et al, 2022 ). Furthermore, increased inosine metabolism may be protective in ALS.…”
Section: Drugsmentioning
confidence: 99%